Optimizing the Application of Office Automation at the DPRD Secretariat of South Sulawesi Province - Darwis, Muh.; Jamaluddin, Jamaluddin; Ramadhani, Ghina (Universitas Negeri Makassar, 2022)
Along with the development of science and technology (IPTEK), the role of information systems in an organization or office is no longer in doubt. Information system support can make an office have a competitive advantage. This study aims to determine the optimization of the application of office automation at the DPRD Secretariat of South Sulawesi Province. Data collection techniques used are observation, questionnaires and documentation. The data analysis technique used is descriptive percentage and distribution analysis. The results showed that the Optimization of the Application of Office Automation at the Secretariat of the DPRD of South Sulawesi Province was in the very good category in terms of Microsoft Word indicators, which were in the very good category including the ease of employees in managing documents. Microsoft Excel indicators are in the very good category including providing convenience in terms of word processing. The Microsoft Outlook indicator is in the good category in terms of optimizing the performance of employees with a work schedule. The Microsoft Power Point indicator is in the good category in this case the presentation can facilitate information, and the Publisher Indicator is in the good category in this case increasing competitiveness through promotions.